2019
DOI: 10.1007/s00167-019-05594-0
|View full text |Cite
|
Sign up to set email alerts
|

Medial unicompartmental knee arthroplasty in ACL-deficient knees is a viable treatment option: in vivo kinematic evaluation using a moving fluoroscope

Abstract: Purpose Unicompartmental knee arthroplasty (UKA), resulting in similar kinematics to native knees, is functionally superior to total knee arthroplasty (TKA). However, ACL deficiency is generally considered to be a contraindication. The main purpose of this study was to investigate if UKA in ACL‐deficient knees would result in similar kinematics to conventional UKA with an intact ACL. Methods Ten conventional UKA patients were compared to eight ACL‐deficient patients with a reduced tibial slope to compensate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Previous studies have proved that the posterior tibial slope is important for accurate knee arthroplasty. 35,36,38 A previous study by Kang et al 39 indicated that posterior TF translation significantly increased as posterior tibial slope increased. The translation of posterior TF is crucial in knee arthroplasty, as a higher degree of flexion is allowed before a TF impingement occurs.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous studies have proved that the posterior tibial slope is important for accurate knee arthroplasty. 35,36,38 A previous study by Kang et al 39 indicated that posterior TF translation significantly increased as posterior tibial slope increased. The translation of posterior TF is crucial in knee arthroplasty, as a higher degree of flexion is allowed before a TF impingement occurs.…”
Section: Discussionmentioning
confidence: 96%
“…Similar trends have been found in various biomechanical studies. 4,12,38 A previous study showed that anterior tibial translations during the Lachman test decreased by approximately 5 mm with an 8° posterior tibial slope. 4 However, no variation in slope altered the pivot shift kinematics in ACL-deficient knees.…”
Section: Discussionmentioning
confidence: 98%
“…Accurate in vivo 6-DOF knee kinematics and articular contact behavior of the knee arthroplasty during functional activities are crucial factors to predict its biotribology and PE wear. However, only partial kinematic parameters of FB UKA have been reported, which is not sufficient in in vitro wear simulation ( Mochizuki et al, 2013 ; Zumbrunn et al, 2020 ). In the current study, the specific in vivo 6-DOF showed different patterns between the stance phase during gait and weight-bearing knee flexion–extension (single-leg lunge and sit-to-stand) for the knee following FB UKA.…”
Section: Discussionmentioning
confidence: 99%
“…The precise and detailed knee kinematics and kinetics of UKA during weight-bearing daily activities can give significant insights into the in vitro UKA simulator’s loading condition when evaluating its wear performance. The knee flexion, tibial internal rotation, and femoral anteroposterior movement of FB UKA during several activities have been reported ( Mochizuki et al, 2013 ; Zumbrunn et al, 2020 ). However, other kinematic parameters were not reported, e.g., knee abduction-adduction; and more demanding daily activities should be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…These results indicate the importance of implant designs in preserving normal knee kinematics in both UKA and TKA. 24,44,45 With regards to role of ACL, Zumbrunn et al 46 compared 10 conventional UKA patients with eight ACL-deficient UKA patients using a moving fluoroscope system, and found that similar kinematic waveforms were seen in both UKA groups, but ACL-deficient group shows a significant posterior femoral shift during the first 25% of deep knee bend. Suggs et al 9 showed that functional ACL is likely needed for increasing odds of long-term success after medial UKA.…”
Section: Discussionmentioning
confidence: 99%